1990
DOI: 10.1152/jappl.1990.68.6.2337
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle oxidative capacity, antioxidant enzymes, and exercise training

Abstract: The purposes of this study were to determine whether exercise training induces increases in skeletal muscle antioxidant enzymes and to further characterize the relationship between oxidative capacity and antioxidant enzyme levels in skeletal muscle. Male Sprague-Dawley rats were exercise trained (ET) on a treadmill 2 h/day at 32 m/min (8% incline) 5 days/wk or were cage confined (sedentary control, S) for 12 wk. In both S and ET rats, catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPX)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
118
3
9

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(152 citation statements)
references
References 0 publications
21
118
3
9
Order By: Relevance
“…Several authors have reported the change in enzymatic antioxidant defenses in response to the exercise. 39,40 In view of the obtained results, we can affirm that acute physical exercise caused different effects in the skeletal muscle and lungs of mice, as demonstrated by the levels of TBARS and antioxidant defenses. In fact, TBARS levels in the skeletal muscle remained increased until 24 h after exercise, while in lungs TBARS levels increased only up to 1 h after exercise.…”
Section: Discussionsupporting
confidence: 62%
“…Several authors have reported the change in enzymatic antioxidant defenses in response to the exercise. 39,40 In view of the obtained results, we can affirm that acute physical exercise caused different effects in the skeletal muscle and lungs of mice, as demonstrated by the levels of TBARS and antioxidant defenses. In fact, TBARS levels in the skeletal muscle remained increased until 24 h after exercise, while in lungs TBARS levels increased only up to 1 h after exercise.…”
Section: Discussionsupporting
confidence: 62%
“…While a few studies suggest that endurance training does not elevate SOD activity in skeletal muscles (Alessio & Goldfarb, 1988;Ji et al 1988;Laughlin et al 1990), most studies indicate a training-induced increase in total SOD activity (Jenkins, 1983;Higuchi et al 1985;Powers et al 1992;Criswell et al 1993;Leeuwenburgh et al 1994Leeuwenburgh et al , 1997Powers et al 1994a,b;Oh-ishi et al 1997a,b).…”
Section: Superoxide Dismutasementioning
confidence: 99%
“…Most studies show that GPX activity is inducible by chronic exercise training in skeletal muscle, including the diaphragm (22,26,79,81,110,112,118). However, GPX adaptation to training appears highly muscle fiberspecific.…”
Section: Antioxidant Enzymesmentioning
confidence: 99%